A CLINICAL STUDY ON EVALUATION OF SUNBURN CASES VISITED TO THE DERMATOLOGY DEPARTMENT - Sanjay Sakarwal; Amit Kumar Kamboj (Journal of Biomedical and Pharmaceutical Research, 2020)
Introduction: The key risk factor for most skin malignancies is exposure to ultraviolet radiation (UVR), and sunburn history, intermittent UVR exposure from the sun and sunbeds, and UVR exposure from these sources are significant contributors to the development of melanoma. The goal of the current study was to evaluate the prevalence of sunburn among the study population. Materials & Methods: The dermatology department was the site of the current study. There were 146 sunburn cases in it that had been reported to the department. The location of the sunburn, a specific age group, and the neighborhood were taken into account in the entire population. The scalp, cheeks, hands, and neck were carefully examined for signs of sunburn. Results: Age group 20-40 years had 45 males and 35 females while 40-60 years had 41 males and 25 females. The difference was significant (P- 0.01). The face (14% for men and 10% for women), followed by the neck (25% for men and 22% for women), the scalp (15% for men and 19% for women), and the hands (12% for men and 9% for women). The distinction was appreciable (P- 0.01). Conclusion: Sunburns are a common type of skin disease. There is no clear sex preference. In the age range of 20 to 40 years, instances are relatively frequent. Key words: UV rays, sunburns on the scalp, etc.